Self-medication with over-the-counter drugs among consumers: a cross-sectional survey in a Southwestern State in Nigeria (2023)
Objectives: This study set out to assess the knowledge, perception and practices of consumers regarding selfmedication with over-the-counter (OTC) drugs, the prevalence of risky practices and their associated factors in pharmacy outlets in Ibadan, Southwestern Nigeria. Setting A cross-sectional study was conducted using an interviewer administered questionnaire. Descriptive statistics and multivariate analysis were performed by using SPSS V.23 with statistical significance set at p<0.05. Participants 658 adult consumers aged 18 years and above. Primary and secondary outcome measures: The primary outcome was self-medication, measured using the following question: A positive answer indicates a selfmedicated participant. Do you practise self-medication? Results: Respondents who had practised self-medication with OTC drugs were 562 (85.4%), of which over 95% were involved in risky practice. Consumers agreed (73.4%) that OTC drugs can be recommended by pharmacists and perceived (60.4%) that OTC drugs are harmless regardless of how they are used. Reasons for practising self-medication with OTC drugs include: if it is a minor condition, I can take the initiative (90.9%), visiting a hospital wastes my time (75.5%) and ease accessibility of the pharmacy (88.9%). Overall, (83.7%) respondents had good practices of handling and use of OTC drugs, while (56.1%) had good knowledge of OTC drugs and identification of OTC drugs. Factors associated with consumer handling and use of OTC drugs in selfmedication were older participants (p=0.01), those with postsecondary education (p=0.02), and who possessed good knowledge (0.02), were more likely to practise selfmedication with OTC drugs. Conclusion The study revealed a high prevalence of selfmedication, good practices towards handling and use of OTC drugs, and moderate knowledge of OTC drugs by the consumers. This underscores the need for policy-makers to introduce measures to enforce consumer education by community pharmacists to minimise the risks of inappropriate self-medication with OTC drugs.